Neoadjuvant Programmed Cell Death Protein 1 Blockade Combined With Stereotactic Body Radiation Therapy for Stage III(N2) Non-Small Cell Lung Cancer: A Case Series - Wang, Zhen; Qiang, Yong; Shen, Qin; Zhu, Xi-Xu; Song, Yong (Frontiers in Oncology, 2022)
The addition of radiotherapy in neoadjuvant chemotherapy did not improve event-free or overall survival in resectable non-small cell lung carcinoma (NSCLC). Neoadjuvant immunotherapy produced major pathologic response(MPR) rate of up to 45%. The potential synergy between radiotherapy and immunotherapy has been described in several studies. We reported outcomes of three cases of stage III/N2 NSCLC treated with neoadjuvant immunotherapy and stereotactic body radiation therapy (SBRT) in a single center. This explanatory trial included treatment-naive patients with stage III resectable NSCLC who received two doses of the programmed cell death protein 1 (PD-1) inhibitor toripalimab after 1 week of receiving SBRT for lung lesions. Thereafter, surgery was planned 4–6 weeks after the second dose. The primary endpoints were safety and feasibility, while the secondary endpoint was the pathologic response rate. Toripalimab combined with SBRT as a neoadjuvant treatment had well-tolerable side effects and did not lead to a delay in surgery. Among the included patients, one achieved pathologic complete response (PCR), one achieved MPR, and one with 20% residual tumor did not achieve MPR. There were few side effects of toripalimab combined with SBRT as a neoadjuvant treatment, and the treatment did not cause a delay in surgery. This study preliminarily explored the outcomes of a new neoadjuvant treatment. .